Hypercalciuria and nephrolithiasis: Expanding the renal phenotype of Donnai‐Barrow syndrome. Issue 1 (13th March 2018) - Anglani, F.; Terrin, L.; Brugnara, M.; Battista, M.; Cantaluppi, V.; Ceol, M.; Bertoldi, L.; Valle, G.; Joy, M.P.; Pober, B.R.; Longoni, M.
Abstract : Whole exome sequencing detected novel likely pathogenic variants in LRP2 gene in 2 patients presenting with hearing and vision loss, and the Dent disease (DD) classical renal phenotype, that is, low molecular weight proteinuria (LMWP), hypercalciuria and nephrocalcinosis/nephrolithiasis. We propose that a subset of patients presenting as DD may represent unrecognized cases or mild forms of Donnai‐Barrow/facio‐oculo‐acustico‐renal (DB/FOAR) syndrome or be on the phenotypic continuum between the 2 conditions.